Raspberry Pi and Arduino : go to the next level. (Packt Publishing, 2022)
Create your own custom projects with Raspberry Pi and Arduino About This Video Use Raspberry Pi as the "brain" and Arduino as the "muscles" of your application Practice with nine activities and one big final project Develop an engineering mindset when solving problems In Detail Working only with Raspberry Pi, or only with Arduino, is already nice: you can do a lot of projects. But sometimes, this is not enough. You will need to combine the strength of both boards: the power of software with Raspberry Pi (brain) and the closeness to hardware with Arduino (muscles). In this course, we will start with the setup and then progress through four different parts. First, you will learn how to communicate with Serial between Raspberry Pi and Arduino. Then, learn how to build the Arduino circuit for the project, one component at a time. Control Arduino components from the Raspberry Pi. Next, we will explore new Raspberry Pi functionalities such as a camera and Telegram bot then you will learn how to control the camera from the Arduino and send commands to Arduino from a Telegram chat. In the last section, we will work on building a complete Intercom project using Serial, Telegram Bot, Pi Camera, and more. By the end of this course, you will be able to create your own custom projects with Raspberry Pi and Arduino. Audience This course is intended for creators of Arduino and/or Raspberry Pi who wish to combine the two boards for more exciting and challenging projects, or for anybody interested in developing serious robotics or home automation projects using Arduino and Raspberry Pi. As we won't cover the fundamentals of either Python or C++ programming, this course is not suitable for total beginners. Having a solid understanding of both Arduino and Raspberry Pi will definitely help you get started; however, you don't need to be an expert.